Neural differences of inhibitory control between adolescents with obesity and their peers. Issue 10 (October 2018) - Chen, Siqi; Jia, Yajun; Woltering, Steven
Abstract Background/objective Inhibitory control, the ability to suppress prepotent responses and resist irrelevant stimuli, is thought to play a critical role in the manifestation and maintenance of obesity in adolescents. Adolescence is a unique developmental stage characterized by significant maturational changes in cortical structures (i.e., prefrontal cortex: PFC) that relate to inhibitory control processes. The current study investigated the behavioral and neurophysiological correlates of inhibitory control in adolescents with obesity. Subjects/methods We compared 18 normal-weight and 22 adolescents with obesity on performance and electroencephalography (EEG)-based measures during a Go/NoGo task. We investigated N2 and P3 event-related potential (ERP) components. Results Adolescents with obesity showed lower accuracy compared to their normal-weight peers in NoGo trials where greater amounts of inhibitory control effort were required (p  = 0.03). Adolescents with obesity had larger NoGo N2 amplitude relative to the Go N2 amplitude (p  = 0.03), whereas this difference was not observed in the healthy weight sample. Furthermore, a lower self-efficacy of individual's ability to control eating behaviors in challenging situations (as measured by the Weight Efficacy Lifestyle-Short Form) directly correlated with larger NoGo N2 amplitudes for both obese (p  = 0.03) and normal weight groups (p  = 0.01). Conclusions These findings suggested that obesity in adolescence is associated with a decreased ability to modulate cognitive conflict during the inhibitory control processing. The individual differences in conflict monitoring during situations where greater amounts of inhibitory control effort were required might provide an explanation for overeating behaviors in obese adolescents.